Utility of local flaps in the reconstruction of oncologic resection defects of the oral cavity - Munnangi, Ashwini; Dravid, Chandrasekhar; Gatla, Nagarjuna R.; Ram, Priya S.; Mahantshetty, Umesh (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2022)
Background: Objectives of the study were: to report on the utility of local flaps for oral cavity reconstruction in patients undergoing radical surgery for oral cavity cancers, to enumerate different local flaps used for oral cavity reconstruction, and to assess survival and sequelae associated with various flaps. Methods: The study is a retrospective analysis of data on patients with oral cancer treated with resection and local flap reconstruction between January 2018 to February 2021. The study includes patients treated at a tertiary care cancer hospital in South India. Patients of oral cancer who underwent resection followed by local flap reconstruction between January 2018 to February 2021 were included. Data was analysed for the extent of resection and type of flap used. Details of flap outcomes in the form of major and minor flap loss, functional outcomes and sequelae if any, were documented. Results: 46 patients, 15 women and 31 men, were included in our series. The median age was 51.5 years with an interquartile range (IQR) of 20.5. Tongue was the most common subsite (n=26; 56.5%) followed by buccal mucosa (n=7; 15.2%). Of the 46 flaps done, the most commonly employed flap was the facial artery myo-mucosal flap (FAMM flap) (n=27;58.6%) followed by the nasolabial flap (n=7;15.2%). There was no case of complete flap loss. Grade II trismus (n=5) was the main sequela observed in this study. Conclusions: Local flaps are a reliable option in oral cavity reconstruction post oncologic ablation.